Adipose derived mesenchymal stem cells along with Alpinia oxyphylla extract alleviate mitochondria-mediated cardiac apoptosis in aging models and cardiac function in aging rats. (10th January 2021) - Chang, Yung-Ming; Shibu, Marthandam Asokan; Chen, Chih-Sheng; Tamilselvi, Shanmugam; Tsai, Chuan-Te; Tsai, Chin-Chuan; Kumar, Kannan Ashok; Lin, Hung-Jen; Mahalakshmi, B.; Kuo, Wei-Wen; Huang, Chih-Yang
Abstract: Ethnopharmacological relevance: The Fructus (Alpinia oxyphylla MIQ ) known as Yi Zhi Ren in Chinese medicine has been used as a food and herbal medicinal substance in China for centuries; in the year 2015 Chinese Pharmacopoeia Commission reported water extracts of Alpinia oxyphyllae Fructus (AoF) as a popular medication for aging-related diseases in the form of tonic, aphrodisiac, and health-care food in south China. Aim of the study: Adipose mesenchymal stem cells are physiologically and therapeutically associated with healthy vascular function and cardiac health. However aging conditions hinder stem cell function and increases the vulnerability to cardiovascular diseases. In this study, the effect of the anti-aging herbal medicine AoF to enhance the cardiac restorative function of adipose-derived mesenchymal stem cells (ADMSCs) in aging condition was investigated. Materials and methods: Low dose (0.1 μM) Doxorubicin and D-galactose (150 mg/kg/day for 8 weeks) were used to respectively induce aging in vitro and in vivo . For In vivo studies, 20 week old WKY rats were divided into Control, Aging induced (AI), AI + AoF, AI + ADMSC, AI + AoF Oral + ADMSC, and AI + AoF treated ADMSC groups. AoF (100 mg/kg/day) was administered orally and ADMSCs (1 × 10 6  cells) were injected (IV). Results: AoF preconditioned ADMSC showed reduction in low dose Dox induced mitochondrial apoptosis and improved DNA replication in H9c2 cardiomyoblasts. In vivo experiments confirmed that both a combined treatment with AoF-ADMSCs and with AoF preconditioned ADMSCs reduced aging associated cardiac damages which was correlated with reduction in apoptosis and expression of senescence markers (P21 and β-gal). Survival and longevity markers were upregulated up on combined administration of AoF and ADMSCs. The cardiac performance of the aging-induced rats was improved significantly in the treatment groups. AoF along with ADMSCs might activate paracrine factors to restore the performance of an aging heart. Conclusion: Hence, we propose that ADMSCs combined with AoF have promising therapeutic properties in the treatment of healthy aging heart. Graphical abstract: Image 1